2011
DOI: 10.1159/000324449
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Controlled Breathing during Pulmonary Rehabilitation in Patients with COPD

Abstract: Background: Conventional pulmonary rehabilitation programs improve exercise tolerance but have no effect on pulmonary function in patients with chronic obstructive pulmonary disease (COPD). The role of controlled breathing using respiratory biofeedback during rehabilitation of patients with COPD remains unclear. Objectives: To compare the effects of a conventional 4-week pulmonary rehabilitation program with those of rehabilitation plus controlled breathing interventions. Methods: A randomized controlled trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 100 publications
0
27
0
2
Order By: Relevance
“…Although the trials were of a small size, the heterogeneity was low (I 2 = 0%). Van Gestal et al 208 reported no difference in the CRQ at 4 weeks' follow-up (0.17, 95% CI -0.09 to 0.43 points) ( Figure 34; see also Figure 31). …”
Section: Breathing Techniquesmentioning
confidence: 94%
See 2 more Smart Citations
“…Although the trials were of a small size, the heterogeneity was low (I 2 = 0%). Van Gestal et al 208 reported no difference in the CRQ at 4 weeks' follow-up (0.17, 95% CI -0.09 to 0.43 points) ( Figure 34; see also Figure 31). …”
Section: Breathing Techniquesmentioning
confidence: 94%
“…In the trials that provided data on the gender of the participants, males tended to be in the majority. Thirty-four trials 66,67,69,70,74,111,112,118,127,133,136,142,144,[151][152][153]168,185,192,195,199,[201][202][203][204][205]209,210,212,214,218,238,264,[270][271][272] did not report the FEV 1 % pred but reported the proportions within severity groups. Of the trials that did provide these data, the mean FEV 1 % pred of the trial participants ranged from 26.3% to 69.0%.…”
Section: Population Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies of low 26 and high 1,2,8,45 methodological quality reported the relationship between autonomic function and physical activity, physical fitness, and exercise capacity in subjects with COPD. Camillo et al 1 concluded that total daily energy expenditure, daily energy expenditure in activities requiring Ͼ3 metabolic equivalents, number of steps/d, and time spent daily in activities demanding Ͼ3 metabolic equivalents significantly affected SDNN (0.36 Ͻ r Ͻ 0.60, P Ͻ .05).…”
Section: Pulmonary Function and Respiratory Parametersmentioning
confidence: 99%
“…1 Patients with COPD have features that encompass several body systems, such as inflammation of the airways, cachexia or obesity, structural and functional changes in respiratory and peripheral muscles, arrhythmias, fatigue, dyspnea, poor quality of life (QOL), reduced exercise capacity, depression, anxiety, and sleep disturbances. [1][2][3][4][5][6][7][8] More recently, COPD has been reported to adversely affect the autonomic nervous system. 2,5,6 Consequently, autonomic function in patients with COPD has received a considerable amount of attention in the literature.…”
Section: Introductionmentioning
confidence: 99%